Three-dimensional computational study in a corrugated pipe inserted system filled with phase change material - Akbal, Omer; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal H. (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this paper is to make a three-dimensional computational analysis of melting in corrugated pipe inserted system filled with phase change material (PCM). The system was heated from the inner pipe, and temperature of the outer pipe was lower than that of inner pipe. Different geometrical ratio cases and two different temperature differences were tested for their effect on melting time. Design/methodology/approach A computational analysis through a pipe with corrugated pipe filled with PCM is analyzed. Finite volume method was applied with the SIMPLE algorithm method to solve the governing equations. Findings The results indicate that the geometrical parameters can be used to control the melting time inside the heat exchanger which, in turn, affect the energy efficiency. The fastest melting time is seen in Case 4 at the same temperature difference which is the major observation of the current work. Originality/value Originality of this work is to perform a three-dimensional analysis of melting of PCM in a corrugated pipe inserted pipe.
Keywords: Melting; PCM; Heat exchanger; Corrugated wall; 3D solution